1978
DOI: 10.1021/bi00601a019
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of protein cross-links

Abstract: The thermal transitions of native lysozyme and a well-characterized cross-linked derivative of lysozyme [Imoto, T., and Rupley, J. A. (1973), J. Mol. Biol. 80, 657] have been studied in 1.94 M guanidine hydrochloride at pH 2. The observed increase in the melting temperature from 32.4 degrees C for native lysozyme to 61.8 degrees C for the cross-linked derivative corresponds to a calculated 5.2 kcal/mol increase in the free energy of denaturation. This free-energy change is attributed to the decreased entropy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…Assuming the stability to be related linearly to the urea concentration [23], the conformational stability of IIIn in the absence of urea is likely to be only half the 10.6 kcal/mol estimated for native RNase [24]. This decrease in stability of 5 kcal/mol is about that expected simply for the absence of 1 covalent crosslink [25].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the stability to be related linearly to the urea concentration [23], the conformational stability of IIIn in the absence of urea is likely to be only half the 10.6 kcal/mol estimated for native RNase [24]. This decrease in stability of 5 kcal/mol is about that expected simply for the absence of 1 covalent crosslink [25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HEL was stabilized by cross-linking between K1 and H15 with an alkyl chain (1-15 CL-HEL) (29) and by cross-linking between E35 and W108 through an ester bond (35-108 CL-HEL) (21,30). These modified amino acids are shown in the three-dimensional structure of HEL (Fig.…”
Section: Preparation Of Modified Lysozymes and Their Stabilitiesmentioning
confidence: 96%
“…RNase Thl was found less stable to heat than the intact protein (-ATm 16"C), whereas RNase Th2 was fully unfolded at room temperature. The peptide bond hydrolysis is expected to destabilize a protein for purely entropic reasons, analogous to the reductive cleavage of a disulfide bond in a protein (Johnson et al, 1978;Pace et al, 1988). In fact, the destabilization due to fission of a covalent bond is related to the entropy gain in the denatured state, even if enthalpy and heat capacity effects may be included (see Krokoszynska & Otlewski, 1996, for a recent discussion).…”
Section: Structure-stability-function Of Nicked Rnasementioning
confidence: 99%